Disparities in hepatocellular carcinoma survival by Medicaid-status: A national population-based risk analysis. Issue 4 (April 2023) - Kim, Eric J.; Ganga, Arjun; Lee, James Y.; Zawadzki, Roy S.; Adriance, William; Wang, Rachel; Cholankeril, George; Somasundar, Ponnandai S.
Abstract: Background: Previous studies have demonstrated disparities in survival surrounding hepatocellular carcinoma (HCC) across a variety of socio-demographic factors; however, the relationship between Medicaid-status and HCC survival is poorly understood. Methods: We constructed 5-year, disease-specific survival curves using the Kaplan-Meier method and performed an adjusted survival analysis using multivariate Cox-proportional hazard regression. Results: We analyzed 17, 059 non-elderly patients (12, 194 non-Medicaid, 4875 Medicaid) diagnosed between 2006 and 2013 and found that Medicaid status was not associated with higher risk of diseases-specific death compared to other insurance types (p = .232, aHR 1.02, 95% CI: 0.983–1.07) after for controlling for a variety of co–variates (ie. marital status, urbanicity, etc.). We found no difference in the risk of death between patients enrolled in Medicaid for more than three years versus those enrolled for less than three years. In all models, rurality and unmarried status were also associated with an increased risk of death (aHR 1.11, 95% CI: 1.03–1.18, p = .002 and aHR 1.18, 95% CI: 1.13–1.23, p < .001, respectively). Discussion: Those enrolled in Medicaid prior to HCC diagnosis may not be associated with a higher risk of disease-specific death compared to non-Medicaid enrolled patients.